Digital Transition and Waste Management in Architecture, Engineering, Construction, and Operations Industry - Pellegrini, Laura; Campi, Stefano; Locatelli, Mirko; Pattini, Giulia; Di Giuda, Giuseppe Martino; Tagliabue, Lavinia Chiara (Frontiers in Energy Research, 2020)
The research aims at analyzing the integration of Waste Management (WM) strategies and Information management in the construction procurement process. The application of BIM methodologies for a Most Economically Advantageous Tender could address the digital transition in order to adopt environmentally sustainable practices. Despite the wide regulation regarding waste minimization, an overview of which is provided, AECO is still one of the most polluting industrialized sector. Drivers and barriers to the method, and a literature review are provided: BIM approaches to enable WM practices have been analyzed from the designer and constructor’s point of view, but few studies investigated the role of the Client, in particular the Public Client. The goal of the study was to evaluate the efficiency of Most Economically Advantageous Tender and a BIM methodology to promote WM strategies during the tender phase. Design Built (DB) and Design Bid Built (DBB) procurement models are tested through three case studies of Italian schools’ calls for proposals: the BIM model enabled to verify the bids in terms of WM strategies implementation. Blockchain and Smart contract future applications are also investigated in order to ensure transparency of the whole process. The Public Client could trigger a change in the construction sector regarding the integration of WM practices, as a central and active actor of the construction process, through the application of Green Public Procurement and BIM methodologies.